Modification of polysulfone ultrafiltration membranes with PVA and TiO2 for better antifouling - Thanh Phong, Mai; Xuan Thang, Cao; Dinh Tuan, Phan (Vietnam Journal of Science and Technology, 2017)
The objective of this study was to investigate anti-fouling property of modified polysulfone ultrafiltration  (UF) membranes.  Polysulfone UF membranes were modified  by  coating  a  thin film of polyvinyl alcohol (PVA), or a mixture of polyvinyl alcohol and titanium dioxide (TiO2) on  surface.  Effects  of  curing  temperature  on  the  coated  membranes  were  also  studied.  The modified  membranes  were  tested  with  0.5  g/L  sodium  alginate  solution  and  industrial  dye wastewater.  Curing  temperature  influenced  remarkably  flux  and  fouling  property  of  the membranes. Among experiments studied, 85 oC was the best curing temperature. The PVA and PVA/TiO2-coated membranes reduced fouling significantly. Dispersion of TiO2 nanoparticles on membrane surface improved considerably bacteria removal of the membranes.